YAG Laser for Macular Subhyaloid Hemorrhage - Sharif Hashmani, Sadaf Shah, Imran Ghayoor, Syed Irshad Haider (Pakistan Journal of Ophthalmology, 2012)
Subhyaloid hemorrhage is defined as a localized detachment of vitreous from the retina caused by the accumulation of blood, which can lead to sudden and severe loss of vision, when it takes place in the macular area. Premacular subhyaloid hemorrhage may occur in retinal vascular disorder such as proliferative diabetic retinopathy, branch retinal vein occlusion, macro aneurysm, and age-related macular degeneration, hematological disorders such as leukemia1 and chemotherapy induced pancytopenia, following laser in situ keratomileosis (LASIK)3 because of rapid release of the microkeratome vacume pressure or after retinal vascular rupture associated with physical exertion (valsalva retinopathy),2. Terson’s Syndrome4. Purtscher’s retinopathy5. Sub-hyloid haemorrhage can be managed either conservatively or by vitrectomy6. Hyloidectomy of the posterior hyloid face is another option7,8.